The Use of E-Court In The Settlement of Civil Cases, In Realizing Simple, Fast, And Low-Cost Justice At The Jepara District Court - Tri Sugondo (Asian Journal of Social and Humanities, 2022)
A legal state is a country whose entire aspect of life is governed by law. All actions of the government and its citizens (society) must be submissive, obedient, and obedient to the applicable law, because the law is used as a basis for regulating all aspects of social, national, and state life, in all national and state life. The non-doctrinal approach in this study is intended to find out an overview of how the use of e-court in the settlement of civil cases (lawsuits, simple lawsuits, and applications) in the Jepara District Court. With the e-court, the costs incurred will be less. Through the e-court, the justice-seeking parties register the case, the payment of the costs of the case, summons, trial, and the collection of copies of the judgment are carried out online.